A New Genus and Species of Gall-Forming Fordini (Hemiptera: Aphididae) on Rhus wilsonii Hemsl. from Yunnan, China - Catherine Hébert; Xin Xu; Zixiang Yang; Colin Favret (Insects, 2022)
A new species of gall-forming aphid from China, Qiao jinshaensis gen. et sp. nov., is described from Rhus wilsonii Hemsl. Morphological identification and molecular analyses both support the establishment of a new genus. A diagnosis combining morphological and molecular characters from alate viviparae is provided and specimen metadata are published in an open-access and machine-readable format.